Laying hens fed mycotoxin-contaminated feed produced by Fusarium fungi (T-2 toxin and fumonisin B1) and Saccharomyces cerevisiae lysate: Impacts on poultry health, productive efficiency, and egg quality - Dazuk V.* (2020)
© 2020 Elsevier LtdMycotoxins represent substantial challenges to the farming industry. These include toxins produced by Fusarium fungi, particularly trichothecenes (toxin T-2) and fumonisin (FB1). In the present study, we determined the effects of addition on Saccharomyces cerevisiae lysate (SCL) added to feed contaminated with T-2 and FB1 in terms of health, productive efficiency, and egg laying quality. We used 60 Hy-line Brown laying hens, and divided them into five groups with four repetitions per group and three birds per repetition. There was one group with no contamination with toxin (NoC). The four other groups included combinations of mycotoxin (4 ppm T-2, and 20 ppm FB1): A contamination group was used as control (the C+ group), and another two contained 500 g/ton of SCL (Detoxa Plus®) (the C + D500 group) or 1000 g/ton of SCL (the C + D1000 group). Finally, one group received feed containing 500 g/ton of Detoxa Plus® and 1000 g/ton of Uniwall® MOS 25 (the C + D500 + U1000 group). The experimental period was 84 days, divided into three productive cycles of 28 days each. The NoC hens had greater egg production than the other groups. Hens that consumed feed with SCL had greater egg production than did the C+ group. The NoC hens produced eggs with greater weights than did the C hens; however, C + D1000 and C + D500 + U1000 birds produced greater egg weights than did the C+ group. The C+ group produced lower egg masses than did the NoC and C + D500 + U1000 groups. The feed intake (FI) was lower in hens that ingested mycotoxin. The use of SCL in feed minimized the negative effects of mycotoxin on feed conversion ratio (FI/dozen). Effects of treatment were detected for feed conversion ratio (kg/kg). The hens that consumed mycotoxin had lower shell resistance and thickness compared to those in the NoC group. The red color of egg yolk was greater in the control groups. There were fluctuations in levels of liver enzymes when birds consumed mycotoxin (sometimes reduced and sometimes increased); nevertheless, the cumulative effect increased the activity of alanine aminotransferase. The serum concentration of reactive oxygen species was greater in hens that ingested mycotoxin only on d 84 compared to the NoC group. Serum glutathione S-transferase activity was greater on d 56 in C + D500 and C + D1000 hens than in the others. We conclude that, in general, the consumption of mycotoxin impaired the performance and quality of the eggs of the hens; the addition of the S. cerevisiae lysate and the addition organic acids, yeast cell wall and mineral carrier minimized some of the negative effects caused by T-2 and FB1.